Research on China's holistic teaching design: Theme evolution, realistic confusion and strategy optimization - Yaqiong Li; Wenbin Xu; Yuchen Pan; Yiwen Xu (Psychology, Evaluation, and Technology in Educational Research, 2021)
The introduction of subject literacy, the promulgation of "new curriculum standards", and the implementation and promotion of new teaching materials drive the transformation of school education methods and directly affect the transformation of research on teaching design. Therefore, the research on holistic teaching design focusing on the transformation of classroom teaching methods and pointing to the reform of classroom teaching is of important theoretical value and practical significance. By combing the researches on holistic teaching design of different subjects and different perspectives in the basic education stage, it is found that the relevant theoretical analysis and the holistic teaching design model or strategy provide a certain sense of guidance or reference for teaching practice. However, with the deepening of the holistic teaching design research, the problems in its research have gradually emerged: collaborative research needs to be deepened; the research horizon can be further expanded; the standardization of experimental research needs to be strengthened. Therefore, in terms of holistic teaching design research, it is necessary to explore new collaborative research models and innovate research methods to optimize collaborative research models, so as to promote the effectiveness and in-depth research; it needs to be integrated into interdisciplinary and transdisciplinary perspectives, so as to enhance the innovation of research by deepening discipline research and strengthening interdisciplinary research; experimental research needs to pay attention to the selection of experimental objects, the scientificity of experimental design, and the control of experimental factors, and the standardized analysis of experimental data is required, so as to effectively optimize the holistic teaching design model or strategy and improve the effectiveness and reliability of experimental research.